Clinical Recovery and Well-Being in Tuberculosis with Traditional Unani Adjuvant Therapy (International Journal of Food and Nutritional Sciences, 2022)
Background: Tuberculosis (TB) continues to pose a significant global health challenge despite the availability of effective chemotherapy. Prolonged treatment duration, drug-related adverse effects, delayed recovery, and the emergence of multidrug-resistant tuberculosis (MDR-TB) necessitate exploration of safe adjuvant therapies that enhance clinical recovery and improve patient well-being.Objective: To evaluate the efficacy and safety of a traditional Unani formulation used as an adjuvant to standard anti-tubercular therapy (ATT) in patients with pulmonary tuberculosis.Methods: A randomised, double-blind, placebo-controlled clinical study was conducted on pulmonary TB patients attending Majeedia Unani Hospital, New Delhi. Patients were allocated into two groups: the test group receiving ATT with Unani adjuvant formulation and the control group receiving ATT with a placebo. Clinical symptoms, microbial conversion, radiological changes, haematological indices, and biochemical safety parameters were assessed at baseline and during follow-up. Analysis of data was done as per statistical guidelines..Results: Both groups demonstrated significant clinical improvement with ATT. However, the test group showed faster improvement in appetite and well-being, greater weight gain, improved haemoglobin levels, and more favourable trends in inflammatory markers at three months. Liver and renal function parameters remained within acceptable limits, indicating good tolerance of the Unani adjuvant.Conclusion: The Unani formulation was found to be safe and showed potential benefits as an adjuvant to ATT by enhancing clinical recovery and patient well-being. Larger, multicentric trials are warranted to confirm these findings and explore their role in MDR-TB and high-risk populations.